2016
DOI: 10.3390/su9010038
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Reporting in Family Firms: A Panel Data Analysis

Abstract: Abstract:We analyze the largely unexplored differences in sustainability reporting within family businesses using a sample of 230 non-financial Italian listed firms for the period 2004-2013. Drawing on legitimacy theory and stakeholder theory, integrated with the socio-emotional wealth (SEW) approach, we study how family control, influence and identification shape a firm's attitude towards disclosing its social and environmental behavior. Our results suggest that family firms are more sensitive to media exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 106 publications
(170 reference statements)
4
55
1
9
Order By: Relevance
“…The dummy variable short-term incentive (STI) and long-term incentive (LTI) are used to indicate the inclusion of respective remuneration incentives for executive directors. Based on previous studies, we control for company size (LNTA), leverage (DE), and profitability (ROA) using the natural log of total asset, debt to equity ratio and return on assets, respectively [38][39][40][41][42][43][44].…”
Section: Methodology and Datamentioning
confidence: 99%
“…The dummy variable short-term incentive (STI) and long-term incentive (LTI) are used to indicate the inclusion of respective remuneration incentives for executive directors. Based on previous studies, we control for company size (LNTA), leverage (DE), and profitability (ROA) using the natural log of total asset, debt to equity ratio and return on assets, respectively [38][39][40][41][42][43][44].…”
Section: Methodology and Datamentioning
confidence: 99%
“…This view stresses the strategic nature of the financial statements and related disclosures. As Gavana et al [39] point out, 'Communication plays a fundamental role in recognizing a firm's legitimacy as it informs stakeholders, and society, that organizational behavior is congruent with its values, norms and expectations; non-communication may threaten performance, resource availability and survival'. According to the legitimacy theory, companies with a high commitment to social and environmental issues should be inherently more likely to disclose information on these topics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To the best of our knowledge, no research has taken into account the effect of the ultimate controlling owner nature on the relationship between EM and CSR disclosure. Prior studies have demonstrated that, relative to their non-family counterparts, family firms exhibit either different CSR disclosure practices [21,22] or attitudes towards earnings management [23,24]; therefore, it is of interest to examine the family effect on the relationship between EM and CSR disclosure, namely employing the latter to mask the former.…”
Section: Introductionmentioning
confidence: 99%